Mycophenolate mofetil combination therapy improves survival after liver transplantation: a single-center retrospective analysis - Zahn, Alexandra; Hinz, Ulf; Schemmer, Peter; Stremmel, Wolfgang; Ganten, Tom M. (Annals of transplantation, 2013)
Background - Because the immunosuppressive regimen is a modifiable risk factor after orthotopic liver transplantation (OLT), physicians are nowadays aiming at an optimized and individualized strategy for each patient. The aim of this retrospective study was to examine the impact of different immunosuppressive regimens on the long-term outcome post-OLT based on routine, real-life situations, with particular focus on the subgroups of patients with HCC or HCV. - Material and Methods - Our study included 186 patients who underwent OLT between 1999 and 2008 at the University Hospital Heidelberg, Germany with an available minimum follow-up period of 12 months. Data were collected pre-transplantation, and at 3 months, 6 months, and 12 months post-OLT and every 6 months afterwards. - Results - We found a statistically significant better 5-year survival in the calcineurin inhibitor (CNI) + mycophenolate mofetil (MMF) group vs. CNI - MMF (p=0.01) in the whole study group, in the HCC group (p=0.008), and in the HCV group (p=0.0163). Furthermore, there was a trend towards a prolonged HCV relapse-free 5-year survival rate in the CNI + MMF group of 85.6% vs. 70.8% in the CNI - MMF group, a trend towards a lower incidence of death secondary to infection (30.8% vs. 69.2%), and a trend towards lower rates of acute rejections (22.6% vs. 29%). The type of CNI administered was irrelevant in all respects. - Conclusions - MMF added to immunosuppressive therapy improves patient survival in OLT recipients in general, as well as in patients with HCC and HCV. Prospective studies are needed to determine if a broader application of MMF post-OLT in combination with CNI-tapering could lead to further outcome improvement.
Gesehen am 26.07.2021